2007
DOI: 10.1007/s00109-007-0237-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcription factor activator protein-1 on interleukin-8 expression and enteritis in response to Clostridium difficile toxin A

Abstract: Clostridium difficile toxin A causes acute colitis associated with intense infiltration of neutrophils. Although C. difficile toxin A is known to induce nuclear factor-kappaB-mediated chemokine expression in intestinal epithelial cells, little is known about its effect on the regulation of activator protein-1 (AP-1) by mitogen-activated protein kinase (MAPK). In the present study, we investigated whether the MAPK and AP-1 signaling pathway is involved in interleukin (IL)-8 expression and enteric inflammation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…following kinase inhibitors: PD98059 (an inhibitor of MEK1/2), SB203580 (an inhibitor of p38), and SP600125 (an inhibitor of JNK) [26,27]. The results indicated that pretreatment with SB203580 significantly attenuated Bax expression in mitochondrial fractions from VacA-stimulated eosinophils.…”
Section: H Pylori Vaca Induces Mitochondrial Trafficking Of Activatementioning
confidence: 95%
See 1 more Smart Citation
“…following kinase inhibitors: PD98059 (an inhibitor of MEK1/2), SB203580 (an inhibitor of p38), and SP600125 (an inhibitor of JNK) [26,27]. The results indicated that pretreatment with SB203580 significantly attenuated Bax expression in mitochondrial fractions from VacA-stimulated eosinophils.…”
Section: H Pylori Vaca Induces Mitochondrial Trafficking Of Activatementioning
confidence: 95%
“…Luciferase assay was performed in accordance with the manufacture's instructions (Tropix, Bedford, MA, USA) [14,21]. Recombinant adenovirus containing a dominant-negative p38a mutant (ADV-105) was obtained from Cell Biolabs (San Diego, CA, USA) [26].…”
Section: Transfectionmentioning
confidence: 99%
“…26,28,35,36 The study was approved by the Ethics Committee of Seoul National University Hospital. After the surgical specimens were washed twice in HBSS, the epithelia were removed by scraping the surface with a glass slide.…”
Section: Isolation Of Primary Human Intestinal Epithelial Cellsmentioning
confidence: 99%
“…Recombinant adenovirus containing a dominantnegative p38a mutant (ADV-105) was obtained from Cell Biolabs, Inc (San Diego, CA). Transfection with adenovirus was performed as described previously [39].…”
Section: Plasmids Transfection and Luciferase Assaymentioning
confidence: 99%